2021
DOI: 10.1039/d0cp06544g
|View full text |Cite
|
Sign up to set email alerts
|

Bridging experiment and theory: enhancing the electrical conductivities of soft-templated niobium-doped mesoporous titania films

Abstract: Combined experimental & theoretical approach for the elucidation of structure–property relations in niobium-doped mesoporous titania.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
2
7
0
Order By: Relevance
“…Impedance spectroscopy is a powerful tool to assess the electrical conductivities of thin films deposited on insulating substrates. [31,49] In accordance with our previous results [20,30] for as-prepared mesoporous films prior to catalytic testing, the addition of 15 mol% Ir to TiO x leads to well-conductive materials (≈10 -2 S cm -1 for mp. IrTiO x ), which enables efficient charge transfer kinetics at the electrode during OER catalysis.…”
Section: Impact Of Ald Temperature and Cycle Number On The Electrical...supporting
confidence: 87%
See 1 more Smart Citation
“…Impedance spectroscopy is a powerful tool to assess the electrical conductivities of thin films deposited on insulating substrates. [31,49] In accordance with our previous results [20,30] for as-prepared mesoporous films prior to catalytic testing, the addition of 15 mol% Ir to TiO x leads to well-conductive materials (≈10 -2 S cm -1 for mp. IrTiO x ), which enables efficient charge transfer kinetics at the electrode during OER catalysis.…”
Section: Impact Of Ald Temperature and Cycle Number On The Electrical...supporting
confidence: 87%
“…[26,27] The general synthesis concept relies on the application of a soft template, e.g., an amphiphilic blockcopolymer, as a porogen to produce fully interconnected pore networks with adjustable pore diameters. [26][27][28] The EISA method is well-established and has been previously used to synthesize various mesoporous metal oxides such as SiO 2 , [26] TiO 2 , [29] IrO x , [10] mixed metal oxides such as IrTiO x [20,30] or Nb-doped TiO x , [31] and composite materials such as Pd/TiO 2 , [32] among others.…”
Section: Introductionmentioning
confidence: 99%
“…Ti substitution leads to defect states that may cross the Fermi level so that the doped systems have a conducting ground state. Experimentally, highest conductivity was observed for 25–33 % Nb/Ti substitution, which was also confirmed by theoretical calculations [38] . In our models, 50 % of the Ti atoms of rutile are substituted by M=Sc, Y, V, Nb, or Ta, so that the primitive bulk unit cells have the composition MTiO 4 .…”
Section: Introductionsupporting
confidence: 83%
“…Experimentally, it was observed that 25-33 % Nb/Ti substitution leads to the highest electrical conductivity. [38] In order to reduce the number of possible cation configurations in our models, we replaced every second Ti atom by the previously mentioned transition metals M and obtained primitive unit cells with MTiO 4 stoichiometry, compare Figure 1, or, for the primitive unit cells, Figure S1 in the Supporting Information. Even though methods for modeling random cation distributions exist, for example, special quasirandom structures, [43] we decided to apply symmetry restrictions to our surface models in order to avoid artificial dipole moments.…”
Section: Bulk Optimizationsmentioning
confidence: 99%
“…Briefly, the model-type oxide films are prepared using the well-established EISA approach with block-copolymer micelles as soft template for the introduction of a mesoporous structure [22,23]. It enables synthesis of well-ordered mesoporous thin films with tunable composition, crystallite size and wall thickness [24,25]. The as-synthesized ordered mesoporous films enable a precise investigation of bulk-averaged information (e.g., XRD) and study of local changes in the phase composition, i.e., domain growth on the nanometer scale using microscope methods such as SEM, TEM, and SAED.…”
Section: Introductionmentioning
confidence: 99%